Enhancing Quality of Muslim Worship Practice: the Role of Religiosity and Spirituality to Mindfulness during Prayer (Khusyu’) - Al-Razi, Muhammad Fakhruddin; Nashori, Fuad (Psikis : Jurnal Psikologi Islami, 2025)
Prayers performed without khusyu' are often just a routine of movements and recitations without deep meaning. In fact, khusyu' is the main indicator of the quality of prayer that has not been widely studied quantitatively. This study aimed to investigate the influence of religiosity and spirituality on the level of khusyu' in prayer. Using a quantitative approach with a cross-sectional design, 220 Indonesian Muslim university students were respondents through online scale completion. Data were analyzed using multiple regression. The results showed that simultaneously, religiosity and spirituality have a significant effect on khusyu'. Religiosity in this article is defined as a concept that describes beliefs, attachments, habits, and a sense of belonging to a particular religious teaching, whereas spirituality refers to the concept of human connection with supernatural entities, such as the belief in God in a religion. However, partially, only religiosity has a significant effect, while spirituality does not show a significant effect on khusyu'. This finding indicates that the quality of khusyu' prayer is more closely related to internalized religious attitudes, ritually and cognitively, than to spirituality alone. The implication of this result shows the importance of cultivating religiosity in improving the quality of worship, especially prayer. Further research is recommended to explore other factors, such as understanding the meaning of prayer recitations and situational conditions during worship that may contribute to the achievement of khusyu'.